Comparison of the effect of temperature and water potential on the seed germination of five Pedicularis kansuensis populations from the Qinghai–Tibet plateau - Bao, Gensheng; Zhang, Peng; Wei, XiaoXing; Zhang, Yongchao; Liu, Wenhui (Frontiers in Plant Science, 2022)
Temperature and water potentials are considered the most critical environmental factors in seed germinability and subsequent seedling establishment. The thermal and water requirements for germination are species-specific and vary with the environment in which seeds mature from the maternal plants. Pedicularis kansuensis is a root hemiparasitic weed that grows extensively in the Qinghai–Tibet Plateau’s degraded grasslands and has seriously harmed the grasslands ecosystem and its utilization. Information about temperatures and water thresholds in P. kansuensis seed germination among different populations is useful to predicting and managing the weed’s distribution in degraded grasslands. The present study evaluated the effects of temperature and water potentials on P. kansuensis seed germination in cool and warm habitats, based on thermal time and hydrotime models. The results indicate that seeds from cool habitats have a higher base temperature than those from warm habitats, while there is no detectable difference in optimum and ceiling temperatures between habitats. Seed germination in response to water potential differed among the five studied populations. There was a negative correlation between the seed populations’ base water potential for 50% (Ψb(50)) germination and their hydrotime constant (θH). The thermal time and hydrotime models were good predictors of five populations’ germination time in response to temperature and water potentials. Consequently, future studies should consider the effects of maternal environmental conditions on seed germination when seeking effective strategies for controlling hemiparasitic weeds in alpine regions.